Konstruksi Moderasi Beragama Masyarakat Kalipasir Tangerang: Model Kerukunan Beragama Islam dan Konghucu - Ahmad Suhendra (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
This article analyzes the model of religious moderation in Kalipasir, Tangerang City. In it there are indigenous peoples who are dominated by the Betawi and Sundanese. On the other hand, there are also ethnic Chinese who have lived in the area for a long time. This ethnic diversity also accompanies religious diversity, especially between indigenous Muslims and non-Muslim Chinese. The purpose of this study is to analyze the construction of religious moderation in Kalipasir. With a social construction approach, this study looks at the concept of religious moderation in the practice of the Kalipasir community. This is field research with data collection using a qualitative model. After the data is collected, then it is analyzed using construction theory. The results of the study show that maintaining religious moderation requires an open minded attitude and shared awareness of diversity and all religions teach peace and harmony.